Evaluasi Suplementasi Tepung Daun Kelor (Moringa oleifera L.) terhadap Performa, Kualitas Fisik, Vitamin A: Evaluation of Moringa Leaf Meal (Moringa oleifera L.) Supplementation on KUB Chicken Performance, Physical Quality, Vitamin A and Cholesterol in the Egg - dortiana sijung, maria; Hermana, Widya; Sukria, Heri Ahmad; Astuti, Dewi Apri; Suci, D M (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
This study aimed to evaluate the supplementation of moringa flour (Moringa oleifera L.) on the performance of KUB chickens as well as the physical quality, vitamin A and cholesterol of the eggs. This study used a completely randomized design (CRD), with 4 treatments of moringa flour supplementation (0%, 5%, 10% and 15%) and 6 replications. The measured variables were performance, physical quality, egg vitamin A content and egg cholesterol content. The data were analyzed using analysis of variance (ANOVA) and further tested with Duncan's multiple range test. The rearing duration was 3 months, using a total of 96 24-week-old KUB chickens. The results showed that supplementation of moringa leaf flour up to 15% in feed had no significant effect on production performance or the vitamin A and cholesterol content of eggs, but it significantly increased the egg yolk color score. It can be concluded that the supplementation of 10% moringa leaf flour provides the lowest feed conversion and has higher income/income over feed cost values compared to the control. Key words: cholesterols, KUB chicken, performance, physical quality, vitamin A